2023
DOI: 10.3390/bs13010064
|View full text |Cite
|
Sign up to set email alerts
|

Neo-Piagetian Predictors of Students’ Performance in Science Learning: Evidence from Primary Education

Abstract: This study explores primary school pupils’ knowledge recall and interpretation skills regarding chemical and physical phenomena, in relation to three psychometric variables: logical thinking, field dependence/field independence, and divergent thinking. The participants (N = 375) were in the fifth and sixth grades (aged 11–12) taking an introductory course in science, and they were involved in three tasks related to combustion, dissolution, and mixture separation. The pupils had to complete an instrument, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Third, the explanatory power of R 2 in the regression analysis was relatively low, which may have undermined the results of the study. However, aside from the R 2 value, all other values that assess significance were shown to be appropriate, and although the R 2 value was low, based on other studies that have conducted regression analysis [59][60][61], it was decided that it is possible to conclude even with a relatively low R 2 value. Therefore, it is suggested that future research makes improvements to this study and increases the number of samples to obtain an R 2 value with greater reliability.…”
Section: Limitations and Future Studymentioning
confidence: 99%
“…Third, the explanatory power of R 2 in the regression analysis was relatively low, which may have undermined the results of the study. However, aside from the R 2 value, all other values that assess significance were shown to be appropriate, and although the R 2 value was low, based on other studies that have conducted regression analysis [59][60][61], it was decided that it is possible to conclude even with a relatively low R 2 value. Therefore, it is suggested that future research makes improvements to this study and increases the number of samples to obtain an R 2 value with greater reliability.…”
Section: Limitations and Future Studymentioning
confidence: 99%
“…LCA was used in an exploratory mode since the clusters were not defined a priori, but they emerged from the analysis. Note that elsewhere (Straatemeier et al, 2008;Vaiopoulou et al, 2017;Vaiopoulou and Papageorgiou, 2018;Stamovlasis et al, 2020), the method was used in a confirmatory mode to validate specific mental models explicitly stated in the literature (Vosniadou and Brewer, 1992;Ioannides and Vosniadou, 2002). These proposed mental models/ latent classes were identified and characterized by specific concurrent misconceptions, which, in fact, have been used in the classification process to obtain those mental models.…”
Section: Interpretation Of the Findings And Theoretical Perspectivesmentioning
confidence: 99%
“…Among them, latent class analysis (LCA) assumes that both observable and latent variables are categorical, and it is the proper measurement model for the coherent knowledge theory since the latter considers the children's mental models as a categorical type of entities. Its applications have been demonstrated in exploratory and confirmatory approaches (Straatemeier et al, 2008;Vaiopoulou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%